2013
DOI: 10.12741/ebrasilis.v6i3.314
|View full text |Cite
|
Sign up to set email alerts
|

Lutzomyia wellcomei Fraiha, Shaw & Lainson (Diptera, Psychodidae, Phlebotominae) em Fragmento de Mata Atlântica do Rio Grande do Norte, Nordeste do Brasil

Abstract: Abstract. Leishmaniasis can affect humans and animals in visceral or cutaneous forms. The cutaneous form has been associated, among other species, with Lutzomyia wellcomei Fraiha, Shaw & Lainson, initially found in the Amazon region. The present study is based on monthly collections from January to December in an Atlantic Forest remnant and a peridomestic environment, using CDC light traps. This is the first systematized study of the specie in Rio Grande do Norte State. The insects were metalized under carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Along with L. whitmani and L. intermedia, L. wellcomei has been recognized as a vector of L. braziliensis in wild settings of northeastern Brazil [ 44 ]. Since L. wellcomei occurs almost exusively during the rainy season and maintains the typical behavior of a wild species [ 45 ], it was classified as an accessory species in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Along with L. whitmani and L. intermedia, L. wellcomei has been recognized as a vector of L. braziliensis in wild settings of northeastern Brazil [ 44 ]. Since L. wellcomei occurs almost exusively during the rainy season and maintains the typical behavior of a wild species [ 45 ], it was classified as an accessory species in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…P. wellcomei , the third most abundant species in this study, was initially found in the Brazilian Amazon [ 39 ] and later in the Northeast, in forests in Ceará state [ 33 ], forest and peridomiciliary environments in Maranhão state [ 13 , 40 ], and in forest environments of metropolitan regions in the states of Pernambuco [ 35 ] and Rio Grande do Norte [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…ATL exhibits different causative agents and vectors, depending on the region of the country [ 5 – 12 ]. Among the sand flies considered vectors of ATL in Brazil, Nyssomyia whitmani, Nyssomyia intermedia , Nyssomyia umbratilis , Migonemyia migonei, Psychodopygus complexa and Psychodopygus wellcomei occur in the Northeast [ 6 , 12 – 15 ]. Effective measures to control the vectors are increasingly necessary.…”
Section: Introductionmentioning
confidence: 99%